Abortion services during the COVID-19 pandemic: a systematic review - Kowsar Qaderi; Rasa Khodavirdilou; Mehri Kalhor; Bahar Morshed Behbahani; Maryam Keshavarz; Maryam Hassanzadeh Bashtian; Mahsa Dabir; Morvarid Irani; Elham Manouchehri; Maryam Farmahini Farahani; Manthar Ali Mallah; Ahmadreza Shamsabadi (BMC, 2023)
Abstract Evidence suggests that COVID-19 may impair access to sexual and reproductive health services and safe abortion. The purpose of this systematic review was investigating the changes of abortion services in the COVID-19 pandemic era. We searched PubMed, Web of Science and Scopus for relevant studies published as of August 2021, using relevant keywords. RCT and non-original studies were excluded from the analysis and 17 studies of 151 included in our review. Requests to access medication abortion by telemedicine and demand for self-managed abortion were the main findings of identified studies. Women requested an abortion earlier in their pregnancy, and were satisfied with tele-abortion care due to its flexibility, and ongoing telephone support. Presenting telemedicine services without ultrasound has also been reported. Visits to clinics were reduced based on the severity of the restrictions, and abortion clinics had less revenue, more costs, and more changes in the work style of their healthcare providers. Telemedicine was reported safe, effective, acceptable, and empowering for women. Reasons for using tele-abortion were privacy, secrecy, comfort, using modern contraception, employing of women, distance from clinics, travel restrictions, lockdowns, fear of COVID-19, and political reasons (abortion prohibition). Complications of women using tele-abortion were pain, lack of psychological support, bleeding, and need to blood transfusions. The results of this study showed that using telemedicine and teleconsultations for medical abortion in the pandemic conditions may be extended after pandemic. Findings can be used by reproductive healthcare providers and policy makers to address the complications of abortion services. Trail registration This study is registered in PROSPERO with number CRD42021279042